2018
DOI: 10.1002/cam4.1530
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of AGR2, p21, and cyclin D and alterations in p53 function were associated with tumor progression and chemotherapy resistance in epithelial ovarian carcinoma

Abstract: Anterior gradient 2 protein belongs to a family of chaperone‐like proteins, namely protein disulfide isomerase. Generally, AGR2 is highly expressed in mucus‐secreting cells and endocrine organs, and in this study, we aimed to evaluate AGR2 and cell cycle molecules in epithelial ovarian cancer and its implications on prognosis. One hundred seventy‐five patient's samples that were diagnosed with primary epithelial ovarian carcinoma were selected. All the patients were treated with platinum‐taxane standard chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Through the interaction with the proliferating cell nuclear antigen (PCNA),/p21 was able to inhibit DNA replication (Rossig et al, 2001). Our current study showed that p21 was highly expressed in normal tissues but reduced in ovarian cancer tissues, which was associated with better survival of patients, consistent with a previous study (Alves et al, 2018). Indeed, a previous study demonstrated that pyridine derivative-induced ovarian cancer cell senescence occurred through p21 activation (Shang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Through the interaction with the proliferating cell nuclear antigen (PCNA),/p21 was able to inhibit DNA replication (Rossig et al, 2001). Our current study showed that p21 was highly expressed in normal tissues but reduced in ovarian cancer tissues, which was associated with better survival of patients, consistent with a previous study (Alves et al, 2018). Indeed, a previous study demonstrated that pyridine derivative-induced ovarian cancer cell senescence occurred through p21 activation (Shang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The prognostic value of AGR2 remains largely inconclusive. A study demonstrated that higher level of AGR2 was related to less aggressive tumors and better prognosis in epithelial ovarian carcinoma 27 , which is in line with Ames and colleagues who found absence of AGR2 was associated with increased malignancy and tumor progression, and relapse in endometrioid and muinous subtypes 28 . AGR2 overexpression was found to contributed to the poor OS in lung cancer 29 , whereas another study showed that AGR2 overexpression did not show any prongnostic value in non-small-cell lung cancer 30 .…”
Section: Dicussionsupporting
confidence: 75%
“…Therefore, various studies have attempted to elucidate the mechanisms of resistance to overcome or delay the resistance of NSCLC cells (22,23,25,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). In addition, recent comprehensive proteomic technologies display a great opportunity to investigate novel clinically relevant oncogenic pathways that may have been over-looked by cancer gene screens (46,47). AGR2, one of these recently discovered oncogenes related to p53, is directly involved in malignant transformation and is able to act as a survival factor through drug resistance (48).…”
Section: Discussionmentioning
confidence: 99%